Change and climate change in the slope of the Gulf of Mexico. Impacts on coffee production - Granados Ramírez, Rebeca; Medina Barrios, Ma. de la Paz; Peña Manjarrez, Vicente (Revista Mexicana de Ciencias Agrícolas, 2018)
Evidence confirming the negative effects that cause climate variability on agricultural production are increasingly recurrent. To explain, from an environmental perspective, the reduction in harvested areas, associated with physiological changes in addition to the increased incidence of pests and diseases in coffee plantations, several hypotheses have been formulated, which focus primarily on: delays and advances of the wet period, in prolonged periods of drought or torrential rains, or in changes in the effective stroke. Such changes, in particular affecting national coffee production, are of concern, because they threaten markets and hence the local, regional and international economy. Based on the above, this paper identifies and analyzes the impacts of climate change on coffee production, on the slope of the Gulf of Mexico, in the state of Veracruz were extracted anomalies in temperature and precipitation variables models general circulation known as Hadley, Echam and GFDL; same were analyzed using the Thornthwaite climate graphs. The results obtained confirm that there will be changes, climates according to Thornthwaite semiwarm migrate to warm in 2080, because the models staged +4.6 °C increase and precipitation decrease -5.5%; fluctuations will impact on the phenological development, presence of pests and diseases and therefore in production.
Keywords: physiological changes; climate graphs; coffee production yields